Sodium Triphosphate Effect on Encapsulation of Vitamin B6 into Chitosan-Alginate Nanoparticles and Its In Vitro Drug Release Study - Rahman, Aulia; Suherman, Suherman; Suratman, Adhitasari (Universitas Gadjah Mada, 2024)
The in-vitro drug release study of vitamin B6 encapsulated into sodium tripolyphosphate crosslinked chitosan-alginate (B6-TCA) nanoparticles aims to determine the effect of sodium tripolyphosphate on the encapsulation efficiency of vitamin B6 and effectiveness of the nanoparticles to release vitamin B6. The focus of this research is synthesizing and characterizing TCA nanoparticles to encapsulate vitamin B6 as an effective delivery system by studying the kinetics release of vitamin B6. The research resulted in the formation of coarse solid powder nanoparticles in yellowish-white color with a nanoparticle size of 22.55 nm. Sodium tripolyphosphate decreased the percentage of encapsulation efficiency in the B6-TCA nanoparticles as its concentration increased. However, the increasing sodium tripolyphosphate causes a slower release of vitamin B6 from nanoparticles. The encapsulation efficiency of vitamin B6 is 82.04%. The optimum composition of B6-TCA nanoparticles ratio is 2:1:1.5:2, where Korsmeyer-Peppas kinetics model suited its better with the Fickian diffusion mechanism of 0.989 and has the smallest reaction rate constant of 0.039 occurred within 6 h.